A Study on Optimal Control of a COVID-19 Transmission Model with the Significance of Early Screening and Testing Measures - Mohankumar, Nandhini; Rajagopal, Lavanya (Journal of Applied Nonlinear Dynamics, 2026)
In this paper, we present a deterministic SEQIR mathematical model that describes the transmission dynamics of COVID-19 that also includes testing procedures in the quarantine stage. The reproduction number R_0 is derived with some properties of the model. The stability of equilibrium points is analyzed. An objective function is proposed and optimal control strategies are derived using Pontryagin’s Maximum Principle. The existence and uniqueness of an optimality system are demonstrated. Numerical simulations are presented in different scenarios with the control interventions early screening, prevention measures of COVID-19, and following a healthy lifestyle. The main objective of the paper is to eradicate the disease in exposed stage. The chosen control variables helps us to reduce the exposed population.